A Study On Physicochemical And Sensory Characteristics Of Eggless Yellow Cake - Muhammad Nurul Azmi, Aida Firdaus; AZ, Nor Anida; Z, Norasmanizan (Indonesian Food Science and Technology Journal, 2018)
To evaluate the practicability of full substitution of eggs in production of a cake, different concentrations (0.5%, 1.0% and 1.5%) of xanthan gum were used. The results showed that substituting eggs with 0.5% xanthan gum inside a cake produced a harder cake and lower its moisture content, water activity and volume compared to control (1599.66 and 1945.69 g, 28.87 and 26.97%, 0.91 and 0.89, 523.33 and 425.00 cm3, respectively). The sensory evaluation result showed that the addition of 0.5% xanthan gum to an eggless cake received the highest acceptability among other eggless cakes. In conclusion, the addition of 0.5% xanthan gum produced the most promising substitute for eggs in cakes.